Building Urban Mobility through Smart Cities and Sustainable Policies - Herlan, Herlan; Elyta, Elyta; Al Qadrie, Syarif Redha Fachmi; Asriadi, Asriadi (Jurnal Borneo Administrator, 2024)
This study examines how smart cities and sustainable policies build urban mobility. Research data from a highly reputable journal indexed by Scopus yielded 321 documents. The search criteria included the title-abs-key "urban mobility," document type "Article," subject area "Social Science," language "English," source type "Journal," and the exact keyword "urban mobility" for publications between 2019 and 2023. This research employed a qualitative approach with bibliometric analysis. Data analysis was conducted using VOSViewer and NVivo12 Plus software to visualise data in images and graphs. The research findings indicate that urban mobility is a pivotal consideration in urban development projects. The United States emerged with the highest focus on urban mobility, accounting for 47 publications, or 16% of the total. Recent research has particularly emphasised topics related to COVID-19, parking management, bicycle infrastructure, mobility services, mobility patterns, and sustainable urban planning, with a significant concentration in 2021. Notably, urban mobility initiatives have fostered collaboration, with a prominent partnership observed with Universidade de São Paulo (13 publications or 17%). These initiatives underscore the importance of establishing networks, groups, and services to advance the development of smart cities and sustainable urban policies